Inovasi Baru Buah Nanas sebagai Alternatif Pengganti Feromon Kimiawi untuk Perangkap Hama Penggerek Batang (Oryctes rhinoceros L.) pada Tanaman Kelapa Sawit di Areal Tanah Gambut - Riki Candra; Puspa Meganningrum; Muhammad Prayudha; Rini Susanti (AGRIUM: Jurnal Ilmu Pertanian, 2019)
The attack of the Oryctes rhinoceros beetle on oil palm plantations can reduce yield by 60% at the first harvest and cause death by 25% in immature plants. The use of pheromone traps in oil palm plantations is an excellent alternative for controlling horn beetles. The purpose of this research is to find out the new innovation of pineapple as an alternative substitute for chemical pheromones for the trapping of stem borer (Oryctes rhinoceros) in oil palm plants on the peat soil area. This study uses Faktorial Non Faktorial Randomized Block Design (RBD) 5 Treatment in the field. The results of the research that we have done, the highest treatment is in P5 and the lowest treatment is in P0